Peran lembaga perkreditan desa bagi anggota pada masa pandemi Covid-19 - I Wayan Ruspendi Junaedi; Donald Samuel Slamet Santosa; Dermawan Waruwu (Jurnal Manajemen Maranatha, 2021)
This study analyzes the role of village credit institutions (in Indonesian is abberviated LPD) for members during the Covid-19 pandemic. This research is a qualitative phenomenological research. The research was conducted during the Covid-19 pandemic due to observance of health protocols. Research data were collected from primary sources (research informants) with interview techniques, observation, and focus group discussion. The data collected was validated by triangulation of sources and methods. The data were then analyzed using the Spradly domain model analysis technique. The results of the study found three LPD roles for members during the Covid-19 pandemic as follows: (1) productive roles: financial solutions for members based on kinship principles; (2) the role of macro social responsibility: resources for the collective collective of members; (3) the role of micro social responsibility: resources for the needs of individual members.